Redesain Pelabuhan Umum Di Kota Merauke (Pendekatan Arsitektur Post Modern) - Anton Topan; Dina Pasa Lolo; Yustian Y.I Giay (Musamus Journal of Architecture, 2019)
The rapid development of the city of Merauke in terms of development has felt an increase in the city's economy so that it is necessary to develop an infrastructure of sea transportation that is adequate and able to support the economic growth of the community. In the progress of the city, the application of traditional elements into a building design is very influential, especially in the design of port infrastructure so that it can reflect and improve the image of the city's locality. The purpose of this study is to get a design that is able to support the smooth operation of passengers and goods that are safe and comfortable. Getting a design that is able to apply traditional elements of marind. The existence of a port that is really capable of serving the smooth activities of passengers and goods is needed by the community, but when viewed from the existing condition of the existing port facility building, the arrival and departure services at the passenger terminal have not been maximized. Therefore Redesign of the Passenger Terminal Port in Merauke with a new face can provide a complete range of service facilities that support the smooth and comfortable activities of passengers and goods. evaluative method.